2017
DOI: 10.1111/jpy.12519
|View full text |Cite
|
Sign up to set email alerts
|

Diatom life cycles and ecology in the Cretaceous

Abstract: The earliest known diatom fossils with well-preserved siliceous frustules are from Lower Cretaceous neritic marine deposits in Antarctica. In this study, we analyzed the cell wall structure to establish whether their cell and life cycles were similar to modern forms. At least two filamentous species (Basilicostephanus ornatus and Archepyrgus melosiroides) had girdle band structures that functioned during cell division in a similar way to present day Aulacoseira species. Also, size analyses of cell diameter ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 68 publications
1
2
0
Order By: Relevance
“…Early Late Cretaceous Hemiaulus from French amber (Charentes) corresponds to mid-latitude coastal environments (Girard et al, 2008, Girard et al, 2009a, 2009bGirard, 2010). This is consistent with the observation of Jewson and Harwood (2017), who suggested that Early Cretaceous diatoms were restricted to continental margins. Late Cretaceous diatom assemblages (including Hemiaulus) are known from extensive diatomites developed in different geographical zones: the eastern Urals and north-western Siberia (e.g.…”
Section: Long Ranging Hemiaulus: Palaeogeographical and Palaeoecologisupporting
confidence: 93%
“…Early Late Cretaceous Hemiaulus from French amber (Charentes) corresponds to mid-latitude coastal environments (Girard et al, 2008, Girard et al, 2009a, 2009bGirard, 2010). This is consistent with the observation of Jewson and Harwood (2017), who suggested that Early Cretaceous diatoms were restricted to continental margins. Late Cretaceous diatom assemblages (including Hemiaulus) are known from extensive diatomites developed in different geographical zones: the eastern Urals and north-western Siberia (e.g.…”
Section: Long Ranging Hemiaulus: Palaeogeographical and Palaeoecologisupporting
confidence: 93%
“…S5, Supporting Information). A recent study suggested that a thick frustule was crucial for diatom success (Jewson and Harwood 2017). A strong frustule was perhaps also a necessary trait for not just free-living diatoms, but for symbiotic diatoms considering that it provides physical protection, and perhaps a means for keeping an internal symbiont more secure.…”
Section: Resultsmentioning
confidence: 99%
“…The frustules are intricately ornamented, and when viewed in the light microscope, species‐level identifications can be readily made. The silica cell walls may persist for millions of years in sediments with a sufficiently high abundance to reconstruct entire life histories (Jewson & Harwood, ). With global estimates of over 100,000 species (Mann & Droop, ), which occupy most marine and freshwater habitats, diatoms have proven useful as biological indicators of environmental change among many aquatic systems (Smol & Stoermer, ).…”
Section: Diatoms As the Next Model Organism In Resurrection Ecologymentioning
confidence: 99%